The Young, the Old, and the Restless: Demographics and Business Cycle Volatility - Jaimovich, Nir; Siu, Henry E (American Economic Review, 2009)
We investigate the consequences of demographic change for business cycle analysis. We find that changes in the age composition of the labor force account for a significant fraction of the variation in cyclical volatility observed in the G7. Since World War II, these countries have experienced dramatic demographic changes, although details regarding timing and nature differ across countries. We exploit this variation to show that the workforce age composition has a large and significant effect on cyclical volatility. We relate our results to the recent decline in US macroeconomic volatility, finding that demographic change accounts for approximately one-fifth to one-third of this moderation. (JEL E32, J11)